(untitled) (Hematology Meeting Reports, 2009)
Forodesine is a potent, selective, transition state inhibitor (i) of the enzyme purine nucleoside phosphorylase (PNP). It’s mechanisms of action is distinct from other purine nucleoside analogues in that forodesine does not act through interaction with nucleic acid. Selective PNPi leads to intracellular accumulation of dGTP in target lymphocytes and subsequent apoptosis. In vitro, Tcell lymphocytes are sensitive to forodesine. Based on these observations, a series of studies in subjects with cutaneous T-cell lymphoma were performed with single agent forodesine.